MUSLIM PAKISTAN DALAM REPRESENTASI SUPERHERO HOLLYWOOD, SEMIOTIKA TAYANGAN MISS MARVEL - Chandra, Christopher (NIVEDANA : Jurnal Komunikasi dan Bahasa, 2025)
The representation of Asian people in western-produced films is sometimes the subject of discussion, there is a strong allegation that these films contain western discourses on Asians. A handful of researchers who examined the representation of Asians in past films argued that there was an allegation of strengthening the principles of western orientalism through the pananda system in films, some found that this orientalism led to exaggerated stereotypes against Asians, which even showed western superiority. With various racial problems that continue to occur in various parts of the world, the problem of stereotypes by favoring one ethnicity, race, and other nations compared to other groups, has implications for harmonious social relations between these different cultural groups. With John Fiske's semiotic approach (2003, 2010) which looks at the marking system of films, television shows, and moving images. The three sign levels, namely the Reality Sign Level, the Representation Sign Level, and the Ideology Sign Level, are expected to be used to read the sign system in recent shows that contain representations of Asian people, such as in the film Miss Marvel. The Miss Marvel film itself was chosen because it was considered capable of showing the dynamics of Asian culture in it. Whether there is an orientalism value in the film marking system, how it is used to build a perspective of representation will all be answered in the results of this study.